Hybrid Foot Vein Arterialization in No-Option Patients With Critical Limb Ischemia: A Preliminary Report. (February 2019) - Ferraresi, Roberto; Casini, Andrea; Losurdo, Fabrizio; Caminiti, Maurizio; Ucci, Alessandro; Longhi, Matteo; Schreve, Michiel; Lichtenberg, Michael; Kum, Steven; Clerici, Giacomo
Purpose: To describe a preliminary experience in treating no-option critical limb ischemia (CLI) patients with a hybrid foot vein arterialization (HFVA) technique combining open plus endovascular approaches.Materials and Methods: Between May 2016 and January 2018, 35 consecutive patients (mean age 68±12 years; 28 men) with 36 no-option CLI limbs underwent HFVA in our center. All limbs had grade 3 WIfI (Wound, Ischemia, and foot Infection) ischemia, and the wound classification was grade 1 in 4 (11%) limbs, grade 2 in 4 (11%), and grade 3 in 28 (78%). Surgical bypass was done on the medial marginal vein or a posterior tibial vein, followed by endovascular removal of foot vein valves and embolization of foot vein collaterals. A "tension-free" surgical approach was used to treat foot lesions.Results: At a mean follow-up of 10.8±2 months, limb salvage was achieved in 25 (69%) limbs and wound healing in 16 (44%); 9 patients presented an unhealed wound. Eleven (31%) patients underwent a major amputation (2 below the knee and 9 thigh). One patient with an unhealed wound and open bypass died of myocardial infarction.Conclusion: HFVA is a promising technique able to achieve acceptable rates of limb salvage and wound healing in no-option patients generally considered candidates for an impending major amputation. Further studies are needed to standardize the technique and better identify patients who can benefit from this approach.